решите уравнение способом подстановки

{3(х+4у)-4х=2(2х+у),

{7(х-5у)+ 6х=3(х+4у)+27

2

Ответы и объяснения

Лучший Ответ!
2013-05-03T16:15:48+04:00

3(x+4y)-4x=2(2x+y)

7(x-5y)+6x=3(x+4y)+27

3(x+4y)-4x=2(2x+y)

-x+12y-2*(2x+y)=0

-x+12y-4x-2y=0

-5x+10y=0

-5x+10y=0

y=5x/10

y=0.5x

7(x-5y)+6x=3(x+4y)+27
7(x-5*(0.5x))+6x=3(x+4*(0.5x))+27

7*(-1.5x)+6x-3*(x+4*0.5x)-27=0

-4.5x-3*(x+4*0.5x)-27=0

-4.5x-3*3x-27=0

-4.5x-9x-27=0

-13.5x-27=0

x=-27/13.5

x=-2

3(x+4y)-4x=2(2x+y)
3((-2)+4y)-4*(-2)=2(2*(-2)+y)

-6+12y-(-4*2)-2*(2*(-2)+y)=0

-6+12y+8-2*(2*(-2)+y)=0

2+12y-2*(-2*2+y)=0

2+12y-(-8+2y)=0

10+12y-2y=0
 10+10y=0

y=-10/10

y=-1

Ответ: x=-2y=-1.